2020
DOI: 10.1590/0100-29452020572
|View full text |Cite
|
Sign up to set email alerts
|

Mineral contents in the skin and flesh of fruits of apple cultivars

Abstract: Apple is considered a functional food, since it presents considerable contribution in the supply of antioxidants, vitamins and minerals, and its consumption is related to the prevention of various diseases. However, most cultivars released in recent years have been poorly studied regarding their nutritional properties. The aim of this work was to quantify mineral contents in the skin and flesh, of apple cultivars with potential production in southern Brazil. The apple cultivars evaluated were ‘Fuji Suprema’, ‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…In the peel, K and Ca concentrations were 62% and 114% lower when compared with 2018. Likewise, Gomez and Kalcsits (2020) and Valverdi and Kalcsits (2021) also reported lower levels of Ca, K, and Mg in the 2019 (Amarante et al, 2013;Sachini et al, 2020;Schveitzer and Petri, 2019;Volz et al, 2006), which can be attributed to several agronomic and environmental factors, such as crop load, vigor, fertilization management, and water management, among others (Ernani et al, 2008). In our study, lower levels of nutrient concentration in 2019 coincided with higher incidence of GS (Table 2).…”
Section: Resultssupporting
confidence: 64%
“…In the peel, K and Ca concentrations were 62% and 114% lower when compared with 2018. Likewise, Gomez and Kalcsits (2020) and Valverdi and Kalcsits (2021) also reported lower levels of Ca, K, and Mg in the 2019 (Amarante et al, 2013;Sachini et al, 2020;Schveitzer and Petri, 2019;Volz et al, 2006), which can be attributed to several agronomic and environmental factors, such as crop load, vigor, fertilization management, and water management, among others (Ernani et al, 2008). In our study, lower levels of nutrient concentration in 2019 coincided with higher incidence of GS (Table 2).…”
Section: Resultssupporting
confidence: 64%
“…Another previously confirmed property of the apple peel is its antioxidant capacity, which has a higher content of polyphenols and anthocyanins compared to the pulp, which is of great benefit to the consumer [127]. As can be seen from Table 6, the results of the mineral composition of Norwegian apples are similar to those of other fruits grown in other apple/growing regions of the world [114,119,128]. Soil, fertilization and cultivars definitely influence composition, but mineral content has been found to vary not only between cultivars but also between years [129].…”
Section: Apple Fruit Mineral Content and Its Qualitysupporting
confidence: 56%
“…As expected, the mineral composition of the fruit was strongly influenced by soil properties, with the presence of various nutrients in the soil supporting the quality of the grown fruit. The consumption of apples as fresh fruit is associated with the intake of various minerals that affect different metabolic processes in the human body [114]. Meanwhile, the particular role of each nutrient in apple/plant physiology has been subjected to numerous studies to outline plant nutrient requirements and fertilizer use, which is an important part of pomology textbooks [63,115,116].…”
Section: Apple Fruit Mineral Content and Its Qualitymentioning
confidence: 99%
“…Similarly, K, Ca, and P were the most abundant elements in Norwegian organic apples grown in western Norway [ 7 ]. Previous studies have also shown that the peel of apples has a higher mineral content compared to the mesocarp (especially Ca, Mg, P, and K) [ 7 , 34 ], which means that a significant amount of minerals is lost when an apple is eaten without the peel. The Mg content was higher than the Ca content in all samples analyzed in our study.…”
Section: Resultsmentioning
confidence: 99%